2018
DOI: 10.1088/1361-6528/aadeda
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the mechanism for current induced network failure for spray deposited silver nanowires

Abstract: Silver nanowires are one of the prominent candidates for the replacement of the incumbent indium tin oxide in thin and flexible electronics applications. Their main drawback is their inferior electrical robustness. Here, the mechanism of the short duration direct current induced failure in large networks is investigated by current stress tests and by examining the morphology of failures. It is found that the failures are due to the heating of the film and they initiate at the nanowire junctions, indicating tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
0
17
0
1
Order By: Relevance
“…Previous simulation- [37] and experiment-based [29,34,36] studies have also reported that AgNWs break into more discontinuous segments when increasing the heat-treatment temperature. Wang et al [36] investigated the effect of heating temperature on a AgNW film where AgNWs with diameters of 20-30 nm and lengths of 25-30 μm are on a polyethylene terephthalate film.…”
Section: Surface Morphologymentioning
confidence: 80%
See 2 more Smart Citations
“…Previous simulation- [37] and experiment-based [29,34,36] studies have also reported that AgNWs break into more discontinuous segments when increasing the heat-treatment temperature. Wang et al [36] investigated the effect of heating temperature on a AgNW film where AgNWs with diameters of 20-30 nm and lengths of 25-30 μm are on a polyethylene terephthalate film.…”
Section: Surface Morphologymentioning
confidence: 80%
“…The AgNW film heated at 200 • C (not contained in this study) showed the thickening of the AgNWs rather than the fragmentation, while the AgNW film heated at 250 • C (not contained in this study) showed a similar morphology to the AgNW-280 • C. The fragmentation and thickening of AgNWs are guessed as being spontaneous processes to minimize the surface energy and hence the total system energy through self-coalescence. It is believed that the fragmentation is driven by the Rayleigh-Plateau instability in which a fluid spontaneously breaks up into smaller droplets with larger surface-to-volume ratios to reduce the total system energy [31,37,38]. In particular, nanostructured materials including AgNW are more likely to cause self-coalescence owing to the high specific surface area, high surface energy, and hence low thermodynamic stability [39].…”
Section: Surface Morphologymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a current density of 150 mA cm -2 on the AgNW network lm turns out to an extremely high current density of 5×10 6 A cm -2 on individual nanowire [10]. Second, the Joule heating caused by current in cross-linked junctions between nanowires is quite strong due to the high contact resistance, which tends to melt the nanowires to droplets in junctions followed with capillary or Rayleigh instability [9][10][21][22]. Third, the deposition of AgNW networks in nanoscale is not homogeneous, and may cause the non-uniform current ow, resulting in local hotspots and local failures [22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Second, the Joule heating caused by current in cross-linked junctions between nanowires is quite strong due to the high contact resistance, which tends to melt the nanowires to droplets in junctions followed with capillary or Rayleigh instability [9][10][21][22]. Third, the deposition of AgNW networks in nanoscale is not homogeneous, and may cause the non-uniform current ow, resulting in local hotspots and local failures [22][23]. Forth, the surface of pristine AgNW is prone to be corroded with sul des, oxygen, moisture or other chemicals in ambient environment [24][25][26].…”
Section: Introductionmentioning
confidence: 99%